MANAJEMEN KETERAMPILAN KEWIRAUSAHAAN DALAM PENGELOLAAN KAYU BEKAS MENJADI JAM DINDING - Hasanah, Nurul; Misriani, Misriani (Inovatif Jurnal Administrasi Niaga, 2020)
This study aims to determine: (1) The level of customer satisfaction with the service quality of the Amuntai wall clock shop, (2) Service quality that is considered important by customers. Product objective management is to assist companies in developing new products according to customer requirements by adjusting the company's capabilities. Wooden wall clocks are a new idea which today many people think negatively that the times will disappear, because of their diminishing popularity and eventually not being used anymore. The results showed that: (1) Customers were quite satisfied with the service quality of wall clocks. (2) The purpose of this product management is to present a design with a new concept which is expected to improve the innovation climate in this industry. Studies and analyzes conducted in (1) this research include conducting interviews in detail, analyzing parts and materials, material analysis producing data, namely a choice of materials that are deemed appropriate for use in the product. (2) The result of product management is a wall clock design made of wood with a design that can be adjusted to the desires of consumers and there are still other product developments according to the results of previous studies and analyzes. Wall clocks are an important component in supporting daily activities, even though you are equipped with a personal watch whose price may reach millions of rupiah, but have we ever carried out activities without looking at the wall clock. Actually you also need to know if we pay attention to its shape, wall clocks can also add to the aesthetic value of a room. The simple concept is how wide of the wall you want to install the clock on.